Gay Israeli Fathers: Reframing Societal Views on Surrogacy. (April 2022) - Tsfati, Maya; Ben-Ari, Adital
The present study aims to explore gay Israeli fathers' responses and resistance to societal criticism on their decision to become parents through transnational surrogacy. The authors interviewed 39 Israeli gay men who became parents via transnational gestational surrogacy using in-depth, semistructured interviews. Analysis of the interviews suggest that the gay fathers responded to societal perceptions on their choice of surrogacy, which they interpreted as heterosexist and hostile, by relating them to Israeli dominant ideologies and constructing a counter discourse that frames surrogacy as an intimate process fostering gender and parental change. Yet, while the participants portray surrogacy as a catalyst for social change, their accounts are embedded within an Israeli context defined by pronatalist and neoliberal ideologies, showing how accounts of change are intertwined within hegemonic ideologies.